ABOUT LEGAL NATURE AND LEGAL REGULATION OF THE PERMISSIVE RELATIONS IN A SPHERE OF THE NATURE MANAGEMENT AND PROTECTION OF AN ENVIRONMENT - K.I. Apanasenko (Економіка та право, 2018)
There is a large list of permissive documents giving for a using of natural resources or for a negative (potentially negative) in fluence on the environment in the Ukrainian legislation. The legal regime of these documents is regulated in special way. Norms of ecological laws state environmental restrictions for users of natural resources, citizens, enterprises and organizations which activity could affect on the environment. The special law in a sphere of permissive relations state principles of the legal regu lation of relations of giving and cancellation of permissive documents for the economic subjects. The Ukrainian law «On administrative services» regulates procedural rules about cooperation of the permissive organs and the economic subjects (as a kind of administrative services). So an actual question is a question about a legal nature of permissive relations in a sphere of ecology that is a main task of the article. This question was not investigated in the economic legal literature in Ukraine. The dominant position of the scientists in a sphere of administrative law is that «permissive activity» in the ecological sphere is a subject for administrative law regulation. Scientists in a sphere of ecological law write about ecological law nature of this legal institute. The author concluded that such relations are economic legal relations, they are a kind of permissive relations in a sphere of economic activity. The object of analyzed relations is a right to realize economic operations / work in a sphere of exploitation of natural resources or such activity that can make an anthropogenic affect on the environment. A subject of the permissive relations in ecological sphere is natural resources, elements of the environment and the whole environment. Difference between subjects of ecological relations and analyzed permissive relations is the next one. The environment and its components are the objects of the legal protection in the ecological relations but they are the objects of the economic activity’s affects in the economic legal relations.